2020
DOI: 10.1021/acs.est.0c04728
|View full text |Cite
|
Sign up to set email alerts
|

Improving Subnational Input–Output Analyses Using Regional Trade Data: A Case-Study and Comparison

Abstract: Environmentally extended input−output analysis (EE-IO) is widely used for evaluating environmental performance (i.e., footprint) at a national level. Many studies have extended their analyses to the subnational level to guide regional policies. One promising method is to embed nationally disaggregated input−output tables, e.g., nesting a provincial level table, into a global multiregional input−output table. However, a widely used approach to environmental assessment generally disaggregates the trade structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
(158 reference statements)
2
10
0
Order By: Relevance
“…In general, we find that country and industry footprints with a high import share show a higher variability (compare also Figure S2 and S3 in the Additional file 1). This finding is in line with Jiang et al 2020 who found a high correlation between the percentage of the China's material footprint sourced from imports and the error of the footprint introduced by the proportionality assumption [19]. This relationship also seems to explain the overall lower variability of the carbon footprints (with relatively low import shares), compared to material, land, and water footprints (with import shares up to 100%).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In general, we find that country and industry footprints with a high import share show a higher variability (compare also Figure S2 and S3 in the Additional file 1). This finding is in line with Jiang et al 2020 who found a high correlation between the percentage of the China's material footprint sourced from imports and the error of the footprint introduced by the proportionality assumption [19]. This relationship also seems to explain the overall lower variability of the carbon footprints (with relatively low import shares), compared to material, land, and water footprints (with import shares up to 100%).…”
Section: Discussionsupporting
confidence: 88%
“…Recently, Jiang et al (2020) compared the material footprints of China and Chinese provinces based on two approaches: one with the assumption of proportional provincial import shares, and one with the inclusion of detailed data on Chinese inter-provincial trade [19]. They found that the Chinese national material footprint are not significantly influenced by the choice of methods.…”
Section: Literature Review Research Gap and Research Questionmentioning
confidence: 99%
“…The MRIO table constructed in the paper is only at the province-level, and it can be nested into global MRIO tables for the global scale analysis (technical details seen Jiang et al . 39 ).
Fig.
…”
Section: Data Recordsmentioning
confidence: 99%
“…Recently, Jiang et al (2020) compared the material footprints of China and Chinese provinces based on two approaches: one with the assumption of proportional provincial import shares, and one with the inclusion of detailed data on Chinese inter-provincial trade. They found that the Chinese national material footprint is not significantly influenced by the choice of methods.…”
Section: Literature Review Research Gap and Research Questionmentioning
confidence: 99%
“…they only examine how the calculated impacts change when including bilateral trade details for one country/region. Second, all but one study investigate economic effects, with only Jiang et al (2020) considering an environmental impact indicator. The effect of the proportionality assumption on other environmental indicators, such as carbon, land or water footprints, however, have not been investigated so far.…”
Section: Literature Review Research Gap and Research Questionmentioning
confidence: 99%